2004
DOI: 10.1161/01.cir.0000130070.96758.7b
|View full text |Cite
|
Sign up to set email alerts
|

The Microsomal Triglyceride Transfer Protein Gene-493T Variant Lowers Cholesterol But Increases the Risk of Coronary Heart Disease

Abstract: on behalf of the WOSCOPS executive Background-The microsomal triglyceride transfer protein (MTP) transfers lipids into apolipoprotein B-containing lipoproteins for secretion from liver, intestine, and heart. The T-variant of a functional polymorphism in the MTP promoter, MTP-493G/T, has been associated with reduced low-density lipoprotein cholesterol concentrations. We hypothesize that this polymorphism impacts on coronary heart disease (CHD) risk. Methods and Results-The effect of the polymorphism was therefo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
51
0
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 24 publications
4
51
0
2
Order By: Relevance
“…Indeed, some authors reported an association between À493G>T and adiposity as well as between this genotype and LDL particle size (Ledmyr et al 2002;Juo et al 2000). This polymorphism may also be associated with an increased risk of cardiovascular disease without being related to plasma lipoprotein/lipid levels (Ledmyr et al 2004). However, Couture et al found no difference in plasma lipid levels or adiposity indices between carriers and noncarriers of the mutation in the Framingham Offspring study (Couture et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, some authors reported an association between À493G>T and adiposity as well as between this genotype and LDL particle size (Ledmyr et al 2002;Juo et al 2000). This polymorphism may also be associated with an increased risk of cardiovascular disease without being related to plasma lipoprotein/lipid levels (Ledmyr et al 2004). However, Couture et al found no difference in plasma lipid levels or adiposity indices between carriers and noncarriers of the mutation in the Framingham Offspring study (Couture et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the FABP2 genotype did not interact noticeably with the amplitude of response to the dietary intervention (12) . The MTTP gene encodes the microsomial transfer protein (MTP), an intra-cellular protein involved in VLDL and chylomicrons assembly in the liver and small intestine, and shows a common mutation in the promoter sequence (2493 G/T polymorphism) (16,17) . We found that men and women exhibit a different pattern for insulin values at baseline with highest values in T/T men and lowest values in T/T women (12) .…”
Section: Gene Polymorphisms and Diet Interactionsmentioning
confidence: 99%
“…(12). Polymorphisms of MTP have been associated with the serum concentration of low density lipoprotein-cholesterol (13,14) as well as with the susceptibility to coronary heart disease (18) and with longevity (19). We have now examined the relation of the -493G›T polymorphism of MTP to blood pressure and the prevalence of hypertension in community-dwelling Japanese men and women.…”
Section: ------------------------------------------------------------mentioning
confidence: 99%
“…One possible explanation for this discrepancy might be that the phenotype associated with the -493G›T polymorphism of MTP is modulated by visceral obesity and hyperinsulinemia (17). The -493G›T polymorphism was recently shown to be associated with the prevalence of coronary heart disease (18). Furthermore, a haplotype marker of MTP was associated with longevity, suggesting that MTP might modify human life-span (19).…”
Section: Introductionmentioning
confidence: 99%